Effects of Radiation on Materials: 17th International Symposium 1996
DOI: 10.1520/stp16470s
|View full text |Cite
|
Sign up to set email alerts
|

The Modelling of Irradiation Embrittlement in Submerged-Arc Welds

Abstract: Until very recently, the irradiation embrittlement behaviour of submerged-arc welds has been interpreted in terms of two mechanisms, namely a matrix damage component and an additional component due to the irradiation-enhanced production of copper-rich precipitates. However, some of the weld specimens from a recent accelerated re-irradiation experiment have shown high Charpy shifts which exceeded the values expected from the measured shift in yield stress. Microstructural examination has revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…3 (a) through (d), respectively. The dashed line indicates the temperature dependence proposed by Bolton et al [19] for matrix defects normalized to the observed RT hardening. In this previous study, a qualitatively similar general trend was observed at 0.1 dpa, with the hardness decreasing as the irradiation temperature increased, and the level of radiation-induced hardness was nearly the same with or without added Cu at all temperatures.…”
Section: Temperature and Dose Dependence Of Radiation-induced Hardnesmentioning
confidence: 93%
“…3 (a) through (d), respectively. The dashed line indicates the temperature dependence proposed by Bolton et al [19] for matrix defects normalized to the observed RT hardening. In this previous study, a qualitatively similar general trend was observed at 0.1 dpa, with the hardness decreasing as the irradiation temperature increased, and the level of radiation-induced hardness was nearly the same with or without added Cu at all temperatures.…”
Section: Temperature and Dose Dependence Of Radiation-induced Hardnesmentioning
confidence: 93%
“…For Charpy shifts, Δ T 41 J was given by a two or three term equation37 where B ΔT and A ΔT represented Cu precipitation and matrix displacement damage as before; the third term represented the possibility of intergranular embrittlement from grain boundary P segregation as affected by dose, irradiation temperature, time and %P. In many C–Mn steel applications the third term was small, hence both embrittlement and hardening arose from similar two-term mechanisms.…”
Section: Mechanistic Background For Analysis Of Irradiation Hardening...mentioning
confidence: 99%
“…The relationship adopted to model Charpy impact energy data has a form which re¯ects the physical processes involved in neutron radiation damage. Mechanistic models for the eect of neutron irradiation on mechanical properties of steels have been developed by Buswell and Jones (1993) and Bolton et al (1994). According to these models, the changes in Charpy impact energy are due to two dierent hardening processes, copper precipitation and dislocation, and one non-hardening mechanism, grain boundary embrittlement.…”
Section: Modelling Backgroundmentioning
confidence: 99%